Adenoid lymphocyte heterogeneity in pediatric adenoid hypertrophy and obstructive sleep apnea - Zhu, Yaxin; Wang, Shengming; Yang, Yingchao; Shen, Bojun; Wang, Anzhao; Zhang, Xiaoman; Zhang, Xiaoxu; Li, Niannian; Gao, Zhenfei; Liu, Yuenan; Zhu, Jingyu; Wei, Zhicheng; et al. (Frontiers in Immunology, 2023)
Adenoid hypertrophy is the main cause of obstructive sleep apnea in children. Previous studies have suggested that pathogenic infections and local immune system disorders in the adenoids are associated with adenoid hypertrophy. The abnormalities in the number and function of various lymphocyte subsets in the adenoids may play a role in this association. However, changes in the proportion of lymphocyte subsets in hypertrophic adenoids remain unclear. To identify patterns of lymphocyte subsets in hypertrophic adenoids, we used multicolor flow cytometry to analyze the lymphocyte subset composition in two groups of children: the mild to moderate hypertrophy group (n = 10) and the severe hypertrophy group (n = 5). We found a significant increase in naïve lymphocytes and a decrease in effector lymphocytes in severe hypertrophic adenoids. This finding suggests that abnormal lymphocyte differentiation or migration may contribute to the development of adenoid hypertrophy. Our study provides valuable insights and clues into the immunological mechanism underlying adenoid hypertrophy.